712 Gastric Emptying Procedure in Oesophagectomy: Meta-Analysis of Surgical Pyloroplasty vs Nil Intervention. (4th May 2021) - Maleyko, I; Nevins, E J; Brown, S; Nauzan, M; Nazeer, M; Sangheli, A; Kanakala, V
Abstract: Introduction: Surgical pyloroplasty is often performed to reduce the rate of delayed gastric emptying. However, the clinical significance of this is not clear. The aim of this meta-analysis is to compare the rates of delayed gastric emptying, anastomotic leak, pulmonary complications, need for further pyloric intervention, and mortality in those patients undergoing pyloroplasty following oesophagectomy and those who do not. Method: Relevant Randomised Control Trials and Cohort Studies were identified. The first group had no drainage procedure following oesophagectomy, whereas the second group underwent a drainage procedure (pyloroplasty). A random effects meta-analysis model was used to compare the outcomes. Results: 12 papers were utilised in the analysis, comprising a total 2567 patients. No significant differences were found between the two groups with regards to delayed gastric emptying (RR 0.87 [95% CI: 0.47 – 1.62], p = 0.66), anastomotic leak (RR 1.20 [95% CI: 0.82 – 1.74], p = 0.34), pulmonary complications (RR 1.04 [95% CI: 0.79 – 1.37], p = 0.79), need for further pyloric intervention (RR 1.44 [95% CI: 0.87 – 2.37], p = 0.16), and mortality (RR 1.18 [95% CI: 0.43 – 3.23], p = 0.75). Conclusions: Surgical pyloric drainage procedures do not improve outcomes for patients undergoing oesophagectomy, nor does omitting the procedure worsens the outcomes.